Enric Ruiz-Geli : Zoo acuático: Aviario (2002)
Proyecto de renovación urbana en Barcelona con motivo del <Fórum>
Keywords: RUIZ-GELI, ENRIC; BARCELONA; CATALUNYA; ESPAÑA; PROYECTOS; JARDINES ZOOLOGICOS; ACUARIOS